الجزاءات المالية في العقد الإداري: دراسة مقارنة - د. خالد محمد مصطفى المولى (PROSPECTIVE RESEARCHES, 2023)
Inancial penalties in the administrative contract are considered an essential issue for the administration to use its authority and privilege in the direct execution in a way which secures its right to resort to the managerial resolution without referring to the judge. The present study tackles the financial penalties as they stand as an important means for the administration to show its power which copes with the rule of stability of the public utility and insuring the execution of the contracts. These penalties are imposed on the contractor to commit him to the execution of his obligatories in favour of the public. Thus, the administration will be able to perform its growth and economic programmes which the present research has shown.